Rapid Spontaneous Resolution of Fibromatosis Colli in a 3-Week-Old Girl - Paolo Adamoli; Piero Pavone; Raffaele Falsaperla; Roberta Longo; Giovanna Vitaliti; Claudio Andaloro; Serra Agostino; Salvatore Cocuzza (Case Reports in Otolaryngology)
Fibromatosis colli is an uncommon benign, congenital fibrous tumor or pseudotumor of the sternocleidomastoid muscle that manifests in infancy. In some of these patients tightening of the muscle results in torticollis. We report the case of a 3-week-old child, who presented with a neck mass localized in the left side with reduced mobility of the head. The diagnosis of fibromatosis colli was raised by ultrasound sonography. The mass regressed spontaneously within 3 months without surgical or physical treatment.